2012
DOI: 10.1038/tp.2012.112
|View full text |Cite
|
Sign up to set email alerts
|

Responder and nonresponder patients exhibit different peripheral transcriptional signatures during major depressive episode

Abstract: To date, it remains impossible to guarantee that short-term treatment given to a patient suffering from a major depressive episode (MDE) will improve long-term efficacy. Objective biological measurements and biomarkers that could help in predicting the clinical evolution of MDE are still warranted. To better understand the reason nearly half of MDE patients respond poorly to current antidepressive treatments, we examined the gene expression profile of peripheral blood samples collected from 16 severe MDE patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
151
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(163 citation statements)
references
References 81 publications
(120 reference statements)
8
151
0
2
Order By: Relevance
“…We identified 15 candidates (5 overexpressed and 10 underexpressed in S-C vs. NS-C comparison; Supplementary Table S6A). We identified Cenpo, Mpp1 and Tbc1d10c which were genes also dysregulated in our previous human transcriptome data (Belzeaux et al, 2012; already validated from the classical threshold method selection) and identified three additional candidates: Fused in sarcoma (Fus), Immunoglobulin mu binding protein 2 (Ighmbp2), and Nucleotide binding protein 1 (Nubp1) for validation (Supplementary Table S6A, bold genes). Secondly, we extracted genes whose expression variations were negatively correlated between blood and the brain, and were different between S-C and NS-C mice groups.…”
Section: Identification Of New Potential Biomarkers Using Rrho Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We identified 15 candidates (5 overexpressed and 10 underexpressed in S-C vs. NS-C comparison; Supplementary Table S6A). We identified Cenpo, Mpp1 and Tbc1d10c which were genes also dysregulated in our previous human transcriptome data (Belzeaux et al, 2012; already validated from the classical threshold method selection) and identified three additional candidates: Fused in sarcoma (Fus), Immunoglobulin mu binding protein 2 (Ighmbp2), and Nucleotide binding protein 1 (Nubp1) for validation (Supplementary Table S6A, bold genes). Secondly, we extracted genes whose expression variations were negatively correlated between blood and the brain, and were different between S-C and NS-C mice groups.…”
Section: Identification Of New Potential Biomarkers Using Rrho Methodsmentioning
confidence: 99%
“…For example, CMAS, encoding cytidine monophosphate N-acetylneuraminic acid synthetase, regulates brain sialylation, which is important for the development of brain structure and function (Yoo et al, 2015). CMAS was among the short list of blood-based biomarkers from the Redei et al (2014) studies, as well as among the candidate gene list from a transcriptome analysis on a naturalistic cohort of MDE patients responding to antidepressant treatment (Belzeaux et al, 2012). CMAS is also part of the most dysregulated transcripts in the UCMS procedure between stressed mice responding to fluoxetine and stressed mice that were either untreated or not responding to fluoxetine (Supplementary Table S5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations